E-Commerce, Accounting Information Systems, Financial Inclusion, and Financial Performance of SHOPEE UMKM in Surabaya - Maylisa, Azizah Firdausy; Muhdor, Ali; Rahman, Arief; Sanusi, Ruchan; Fauziah, Dien Ajeng (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2025)
The expansion of small and medium-sized enterprises (SMEs) has played a crucial role in driving Indonesia's economic development, including the financial performance of the SMEs themselves, particularly those in Surabaya that utilize e-commerce/online retail platforms like Shopee. The objective of this research is to examine the effects of e-commerce, Systems for managing information in the field of accounting, and the integration of financial services, both partially and simultaneously, regarding the economic outcomes of small and medium-sized enterprises utilizing the Shopee platform in Surabaya. The results from the partial test indicate that e-commerce significantly enhances financial performance, as evidenced by a significance value of 0.003. The variable of the accounting information system also exerts a notable positive influence on financial performance, with a significance value of 0.021. Financial inclusion demonstrates a profound effect on financial performance, with a p-value of 0.000, indicating high statistical significance. These results highlight the significant impact of the three variables in enhancing the financial outcomes of SMEs on Shopee in Surabaya, and the consequences of this can serve as a foundation for crafting policies that foster the growth of SMEs in the digital age.